Human Values in Disposing the Dead: An Inquiry into Cremation Technology. (January 2019) - Prajapati, Vishwambhar Nath; Bhaduri, Saradindu
Technologies and human values both have important bearing on human life and conditions. Unfortunately, the dialogue between them has remained inadequate, at best. While the discourse on human values recognizes various kinds and layers of values, including values that are universally relevant across societies and cultures, research on the interface between values and technology has predominantly focused on technology's interactions with society-specific values. This article is an attempt to broaden the scope of this research by specifically taking the case of cremation technologies. Numerous societal, religious and universal values interplay with each other in matters related to death and the dead. Unlike other technologies, an individual can 'use' cremation technology only once, that too with limited control over his/her choice. Our empirical research finds that a complex interaction of multiple layers of values shapes the form and trajectory of cremation technology. Tracking the debate on the adoption of cremation technology in Europe and India, we find important differences in this interaction across societies.